Influence of Local Post-Buckling Behaviour on Bending of Thin-Walled Elastic Beams with Central Intermediate Stiffeners - Kołakowski, Z.; Teter, A. (Engineering Transactions, 1995)
The influence of the local post-buckling behaviour on bending of thin-walled beams is studied. A "lower bound" approach by KOITER and PIGNATARO [1] enables to determine the overall flexural stiffness of a beam after its local buckling. The results obtained are compared with data reported by other authors.